Occurrences of the Angular Roughshark (Oxynotus centrina Linnaeus, 1758) in the Gulf of Finike and Shortfin Mako (Isurus oxyrinchus Rafinesque, 1810) in the Western Mediterranean, Türkiye - Gokoglu, Mehmet; YÄ±ldÄ±z, Alper; BiÃ§er, Erkan; YÄ±lmaz, Mesut (Acta Aquatica: Aquatic Sciences Journal, 2025)
The Mediterranean Sea experiences some of the highest levels of fishing pressure globally. Cartilaginous fish are the most impacted by this pressure, with their populations declining swiftly in the Mediterranean and across the world. There is limited data about sharks in the Mediterranean region. This research documented three Shortfin Mako sharks (Isurus oxyrinchus Rafinesque, 1810), in the Gulf of Antalya and the Angular Roughshark (Oxynotus centrina Linnaeus, 1758) was recorded for the first time in the Bay of Finike. These species are classified as Critically Endangered (CR) on the IUCN Red List, in the Mediterranean Sea.Keywords: Fishing; Gulf; Shark; Turkey